Proficiency Test Comparison: TOEFL iBT, TOEFL PBT and IELTS - Kent, Moriah M (JET ADI BUANA, 2016)
This paper considers three of the most commonly administered proficiency tests: the TOEFL iBT, TOEFL PBT, and the IELTS. Through a composition and analysis of research investigating each test’s structure, scoring, reliability, and validity, the use of proficiency tests as indicators of a student’s productivity and success at English-speaking universities is examined. Whereas each testing service claims to be the number one proficiency test, a comparison of the research shows proficiency tests can be used as reliable predictors of students’ scholastic aptitude and future performance is inconclusive; however the research does suggest that the TOEFL iBT is the most reliable and valid assessment for all four skills available.